Repeatability and sensitivity of T2* measurements in patients with head and neck squamous cell carcinoma at 3T. Issue 1 (22nd January 2016) - Panek, Rafal; Welsh, Liam; Dunlop, Alex; Wong, Kee H.; Riddell, Angela M.; Koh, Dow‐Mu; Schmidt, Maria A.; Doran, Simon; Mcquaid, Dualta; Hopkinson, Georgina; Richardson, Cheryl; Nutting, Christopher M.; et al.
Abstract : Purpose: To determine whether quantitation of T 2 * is sufficiently repeatable and sensitive to detect clinically relevant oxygenation levels in head and neck squamous cell carcinoma (HNSCC) at 3T. Materials and Methods: Ten patients with newly diagnosed locally advanced HNSCC underwent two magnetic resonance imaging (MRI) scans between 24 and 168 hours apart prior to chemoradiotherapy treatment. A multiple gradient echo sequence was used to calculate T 2 * maps. A quadratic function was used to model the blood transverse relaxation rate as a function of blood oxygenation. A set of published coefficients measured at 3T were incorporated to account for tissue hematocrit levels and used to plot the dependence of fractional blood oxygenation (Y) on T 2 * values, together with the corresponding repeatability range. Repeatability of T 2 * using Bland–Altman analysis, and calculation of limits of agreement (LoA), was used to assess the sensitivity, defined as the minimum difference in fractional blood oxygenation that can be confidently detected. Results: T 2 * LoA for 22 outlined tumor volumes were 13%. The T 2 * dependence of fractional blood oxygenation increases monotonically, resulting in increasing sensitivity of the method with increasing blood oxygenation. For fractional blood oxygenation values above 0.11, changes in T 2 * were sufficient to detect differences in blood oxygenation greater than 10% (Δ T 2 * > LoA for ΔY > 0.1). Conclusion: Quantitation of T 2 * at 3T can detect clinically relevant changes in tumor oxygenation within a wide range of blood volumes and oxygen tensions, including levels reported in HNSCC. J. Magn. Reson. Imaging 2016;44:72–80.